Lung Flare Care: Development of a web resource to improve recovery after COPD exacerbations: A mixed methods study - Alethea Kavanagh; Ruben Hopmans; Carla Gordon; Georgia Roberts; Lauren Palmer; Chooi-Ee Lai; Amy Catlin; Rachel Smith; Marielle Collings; Jessica DeGaris; Christian Osadnik (PLoS ONE, 2025)
Recovery from acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is often sub-optimal. Ensuring patients receive high quality, accessible information regarding their condition and priorities of care is challenging during this time. This project aimed to develop and evaluate the utility and usability of a new, co-designed web resource. Mixed methods co-design principles were employed over a 3-phased study. In Phase 1, content analysis was undertaken of qualitative interviews with 8 patients, 2 carers and 9 multidisciplinary healthcare professionals regarding their experiences during and after AECOPD. Results informed a two-round web-based Delphi survey involving 20 international expert clinician-researchers in Phase 2. Consensus items informed web resource construction in Phase 3, with alpha testing evaluations undertaken by Phase 1 stakeholder participants and beta testing evaluations undertaken of the revised web resource following real-world tablet-device pilot implementation by inpatients during and after AECOPD and their treating therapists. The final resource was presented via webinar to community clinicians and final feedback was captured via online survey. 53/58 items reached consensus during the Delphi survey. Tablet-administered education was feasible. Surveys were completed by 25 inpatients. 80% found the resource useful, 72% reported an increased willingness to participate in pulmonary rehabilitation and 28% indicated they gained new insights or motivation for behavioural change to improve disease management. Follow-up patient evaluations were limited by loss to follow-up (14/25; 56%). Therapists indicated high levels of satisfaction with the resource and perceived improved clinical work efficiencies. Of 21 community clinicians, the median response was ‘strongly agree’ that they ‘would recommend this web resource to patients and/or their carers’. Lung Flare Care is a new web-based educational resource that can aid the delivery of high quality education for best care for people with AECOPD. Further research is needed regarding best implementation recommendations and impact of this novel web resource.